The application of STEM education in science learning at schools in ındustrial areas - Parmin; Sajidan (Journal of Turkish Science Education, 2024)
The purpose of this research was to measure the effect of STEM-based science learning on Work and Energy topic and students‟ five entrepreneurial attitudes as a learning outcome. The five entrepreneurial attitudes assessed in this research were (1) self-confidence, (2) initiative, (3) achievement motive, (4) leadership, and (5) risk-taking. This research employed a quantitative post-test design, which was carried out with 219 students from 12 different schools. Before the learning implementation, 24 teachers from the 12 schools collaboratively developed learning materials to be used as the learning source. The validity value of the learning materials assessed by two educational experts was 20 out of 24 and indicated a sufficient validity. A post-test was used to know the effectivity of STEM-based science learning while the five entrepreneurial attitudes were scored with the questionnaires filled by the students. The Likert scale was utilized to analyze the data. The average post-test score was 86 and indicated the students‟ scores to be in the „good‟ category. Additionally, the average scores of the five entrepreneurial attitudes were (1) 85 for self-confidence, (2) 75 for initiative, (3) 84 for achievement motive, (4) 77 for leadership, and (5) 79 for risk-taking. Therefore, the results of this study suggested that the STEM approach was effective to improve the students‟ entrepreneurial attitudes.